MYB74 transcription factor guides de novo specification of epidermal cells in the abscission zone of Arabidopsis - Wen, Xiaohong; Lee, Chan Woong; Kim, Seonghwan; Hwang, Jae Ung; Choi, Yoon Ha; Han, Soon Ki; Lee, Eunmin; Yoon, Taek Han; Cha, Dong Gon; Lee, Seulbee; Son, Heejeong; Son, Jiwon; et al. (Nature Plants, 2025)
The waxy cuticle layer is crucial for plant defence, growth and survival, and is produced by epidermal cells, which were thought to be specified only during embryogenesis. New surface cells are exposed during abscission, by which leaves, fruits, flowers and seeds are shed. Recent work has shown that nonepidermal residuum cells (RECs) can accumulate a protective cuticle layer after abscission, implying the potential de novo specification of epidermal cells by transdifferentiation. However, it remains unknown how this process occurs and what advantage this mechanism may offer over the other surface protection alternative, the wound healing pathways. Here we followed this transdifferentiation process with single-cell RNA sequencing analysis of RECs, showing that nonepidermal RECs transdifferentiate into epidermal cells through three distinct stages. During this vulnerable process, which involves a transient period when the protective layer is not yet formed, stress genes that protect the plant from environmental exposure are expressed before epidermis formation, ultimately facilitating cuticle development. We identify a central role for the transcription factor MYB74 in directing the transdifferentiation. In contrast to alternative protective mechanisms, our results suggest that de novo epidermal specification supports the subsequent growth of fruit at the abscission site. Altogether, we reveal a developmental programme by which plants use a transdifferentiation pathway to protect the plant while promoting growth.
Keywords: Arabidopsis; Arabidopsis Proteins; Cell Transdifferentiation; Epidermal Cells; Gene Expression Regulation, Plant; Plant Epidermis; Transcription Factors